Distinction between Memory (Mneme) and Reminiscence (Anamnese) in Plato’s Philebus - Rouanet, Luiz Paulo (2020)
Maurizio Migliori (2013) suggests that we can find in Philebus elements to think about the distinction between memory (mneme) and reminiscence (anamnese). Here we will study this dialogue, trying to explore that distinction. The hypothesis is that, differently of what occurs in Menon, in the Philebus the distinction is a mere « immanent » one, in the sense that there are no reference or mention to the notorious « theory of reminiscence » evoked in the Menon, that is, to the idea that knowing consists only in the act of remembering something that was known or viewed in another life. To the end of checking that hypothesis, we will contrast the two dialogues.